(untitled) (Bangladesh Journal of Pharmacology, 2014)
The objective of this study was to confirm the antimycotic potential of a diterpenoid compound taxoquinone, isolated from Metasequoia glyptostroboides against pathogenic isolates of Candida species. The taxoquinone (100 mcg/disc) displayed potential anticandidal effect against Candia albicans KBN06P00076, KBN06P00074, C. glabrata KBN06P00066, KBN06P00068, C. tropicalis KBN06P00682, KBN06P00058, C. parapsilosis KBN06P00060, KBN06P00055, and C. guilliermondii KBN06P00492 and KBN06P00867 as a diameter of zones of inhibition, found in the range of 10 ± 0.6 to 13 ± 1.1 mm. The minimum inhibitory and minimum fungicidal concentrations of taxoquinone against the tested clinical isolates were found in the range of 125 to 500 and 125 to 1,000 mcg/mL, respectively. On the viable counts of the tested fungal isolates, the taxoquinone evoked a remarkable anticandidal effect. Elaborative study of SEM revealed potential detrimental effect of taxoquinone on the morphology of C. parapsilosis KBN06P00060 at MIC concentration. These findings confirmed therapeutic potential of taxoquinone.